Optimasi Potensi UMKM melalui Pelatihan Literasi Digital dan Pembangunan Jaringan Internet Murah - Imelda Imelda; Rinny Meidiyustiani; Subandi Subandi (Indonesian Journal of Emerging Trends in Community Empowerment, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in many regions require internet access to market their products. Affordable internet packages are still very limited. Even if available, they are often managed individually. The need for internet access is critical. The solution is to provide training on internet network infrastructure development and digital literacy. The goal is to improve MSMEs' ability to utilize affordable internet technology to optimize their business potential. The training was conducted face-to-face, involving MSMEs and the surrounding community. The training included outreach on affordable internet, building a simple internet network, digital literacy training, and product marketing practices. The training results demonstrated a significant increase in participants' understanding of internet network concepts and their application to product promotion activities through social media. Participants were able to build a local area network (LAN), perform RJ45 crimping, and independently upload products to digital platforms. This training has had a positive impact on improving MSMEs' digital skills and competitiveness.